Preserving mother tongues remains crucial for cultural identity and diversity amid the homogenizing forces of globalized educational systems - Imron, Aly; Somawati, Ni Putu; Mohammed, Lubna Ali (Yayasan Mitra Persada Nusantara, 2025)
The study of mother tongue is becoming increasingly important in understanding the dynamics of language's relationship to cultural identity, cognition, and society. Mother tongue, as the first language learned from infancy, not only influences the way individuals communicate, but also shapes the way they think and see the world. In the context of globalization which is increasingly accelerating the development of international languages, it is critical to evaluate how mother tongues continue to play an important role in education and the maintenance of cultural identity. This research aims to examine critical thinking regarding the existence and importance of mother tongues in education and cultural sustainability, using a document study approach. The analysis was carried out through a review of relevant literature regarding language policy, the foundational role of mother tongue in academic instruction, and the challenges faced by language minority communities. Based on the results of the analysis, it was found that the mother tongue not only supports better understanding in education but also contributes to the preservation of cultural identity. However, there are major challenges related to global language dominance that could threaten its sustainability. In conclusion, there is a need for policies that support the use of mother tongues in schools and society to maintain a balance between globalization and cultural preservation.